The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/cbdv.200890205
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl Cinnamate Derivatives from Oxalis pes‐caprae

Abstract: During the screening of Mediterranean invasive plants, Oxalis pes-caprae was identified as promising species. The fresh leaves and twigs of the plant were crumbled and extracted with AcOEt. The solution was concentrated, and separated into acidic and neutral fractions. The crude neutral residue was fractionated by chromatographic procedures, followed by structure elucidation on the basis of 1H- and 13C-NMR, and MS data analysis, and six new phenyl cinnamate derivatives were identified. The phytotoxic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Oxalis pes-caprae L. is an invasive weed abundant in Mediterranean zones (DellaGreca et al 2007;Ferrero et al 2015) from which several compounds have been previously identified by DellaGreca et al (2007DellaGreca et al ( , 2009DellaGreca et al ( , 2010DellaGreca et al ( , 2008, such as cinnamate derivatives, aromatic compounds and phenols. In our previous study we also identified luteolin and apigenin derivatives in the leaves of this plant (Gaspar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oxalis pes-caprae L. is an invasive weed abundant in Mediterranean zones (DellaGreca et al 2007;Ferrero et al 2015) from which several compounds have been previously identified by DellaGreca et al (2007DellaGreca et al ( , 2009DellaGreca et al ( , 2010DellaGreca et al ( , 2008, such as cinnamate derivatives, aromatic compounds and phenols. In our previous study we also identified luteolin and apigenin derivatives in the leaves of this plant (Gaspar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oxalis acetosella is rich in β‐carotene, ascorbic acid, tocopherols and xanthophylls and one of the most prolific sources of flavonoids (flavonol glycosides and flavan‐3‐ols), especially rutin (Sircelj et al , ). The isolation and characterisation of new potential allelochemicals from O. pes‐caprae (Bermuda buttercup), an invasive alien weed in Italy, Greece, the Iberian Peninsula and North Africa, have been reported recently (DellaGreca et al , , , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 6 -15 (structures not shown) were identified as p-coumaric acid (6), dihydrocinnamic acid (7), cis-p-coumaric acid (8), cinnamic acid (9), 1,2,3,4-tetrahydro-1-methyl-b-carboline-3-carboxylic acid (10) [9], 3-methoxyphenol (11), 2-methoxyphenol (12), 4-hydroxybenzoic acid (13), 4-(1-hydroxyethyl)phenol (14), and 3-(1-hydroxyethyl)phenol (15) on the basis of their spectral data and/or by comparison with those of authentic samples. Further known compounds were identified as flavones: 5,6,7,8,4'-pentamethoxyflavone (tangeretin, 16), 5,6,7,8,3',4'-hexamethoxyflavone (nobiletin, 17), 5-hydroxy-6,7,8,3',4'-pentamethoxyflavone (5-demethylnobiletin, 18), and 4'-hydroxy-5,6,7,8,3'-pentamethoxyflavone (4'-demethylnobiletin, 19) by comparison with previously reported spectroscopic data [10 -12].…”
mentioning
confidence: 99%
“…Further known compounds were identified as flavones: 5,6,7,8,4'-pentamethoxyflavone (tangeretin, 16), 5,6,7,8,3',4'-hexamethoxyflavone (nobiletin, 17), 5-hydroxy-6,7,8,3',4'-pentamethoxyflavone (5-demethylnobiletin, 18), and 4'-hydroxy-5,6,7,8,3'-pentamethoxyflavone (4'-demethylnobiletin, 19) by comparison with previously reported spectroscopic data [10 -12]. All these compounds were isolated for the first time from O. pes-caprae.…”
mentioning
confidence: 99%